Atypical Socket Repair in aesthetic implant rehabilitation. - Mauricio Toro; Tomás Yoma; Alain Manuel Chaple Gil; Gloria Sánchez; Eduardo Fernández (Editorial Ciencias Médicas, 2019)
Introduction: In implant therapy, adequate alveolar bone volume and favorable alveolar ridge architecture are important considerations to obtain positive functional and esthetic rehabilitation. Objective: Describe prosthodontic treatment in an extraction socket with advanced palatal bone resorption secondary to a root fracture through the use of an implant-supported single fixed prosthesis. Principal case data: 39-year-old male patient, without systemic disease, and completely dentate with no occlusal parafunction. Radiographic examination showed the presence of advanced palatal bone resorption, almost total loss of the palatal plate in all its extension secondary to a root fracture of the maxillary left lateral incisor and a large osteolytic area on the palatal aspect of the root. The procedure consisted in extraction of the maxillary left lateral incisor and eventual regeneration of the palatal plate using a resorbable collagen membrane, which was adapted to the bone defect. Then, particulate cortical bone allograft was compacted into the site. Four months after grafting the extraction site, an implant was placed. Six months after implant placement osseointegration was confirmed, and after several stages restoration with a zirconium dioxide abutment and a full ceramic crown was obtained and followed up for 2 years. Conclusions: Regeneration of the palatal plate was possible through the use of particulate cortical bone allograft and a resorbable collagen membrane adapted to the bone defect and placed in position to recreate the palatal plate. This allowed installation of an implant 4 months after the procedure. This technique allowed esthetic and functional results using a single fixed prosthesis.